Spectral problem for Sturm – Liouville operator with retarded argument which contains a spectral parameter in boundary condition - Acikgoz, M.; Araci, S.; Şen, E. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We prove the existence of wave operators for the multidimensional electromagnetic Schr¨odinger operator in divergent form by the Cook method. Moreover, under certain conditions on the coefficients of the given operator, we establish the isometry of its wave operators and determine the initial domains of these operators.